A combined microinvasive trans-submandibular and nasendoscopy surgical approach to dissect recurrent or radiotherapy-insensitive nasopharyngeal carcinoma - Zhao, Yanming; Fang, Jugao; Zhong, Qi; Zhang, Luo; Wang, Chengsuo; Zhang, Jiamin; Chen, Jiaming; Feng, Ling; He, Shizhi; Ma, Hongzhi; Hou, Lizhen; Lian, Meng; et al. (Frontiers in Oncology, 2022)
Objective To investigate a novel combined microinvasive trans-submandibular and nasendoscopy surgical approach for nasopharyngeal carcinoma involving the parapharyngeal space. Methods Seven patients diagnosed with nasopharyngeal carcinoma involving the parapharyngeal space between May 2018 and April 2021, two males and five females, aged 37–63 years.Six of the 7 patients underwent submental flap preparation and dissection of the lymph nodes in the upper neck and parapharyngeal space on the lesion side. The nasopharynx lesions and tumor margins were dissected under nasal endoscopy. The medial boundary of internal carotid artery separated by open cervical approach was used as the lateral boundary of the tumor to realize en bloc resection of the tumor. Results The patients were preoperatively diagnosed with T2~3N0M0 nasopharyngeal carcinoma, including mucoepidermoid carcinoma (n=2), papillary adenocarcinoma (n=1), and nonkeratinizing squamous cell carcinoma (n=4). The tumors were removed completely, and patients achieved primary healing of the incision. No recurrence and no serious complications were recorded during the 13–48 month follow-up. Conclusion Complete resection of the tumor was obtained in the 7 patients without recurrence and serious complications during the follow-up. The findings of this cohort study suggest that, patients with recurrent nasopharyngeal carcinoma after radiotherapy and radiotherapy-insensitive types of nasopharyngeal carcinoma, the combined microinvasive trans-submandibular and nasendoscopy surgical approach may be considered as an surgical options. The results of this study provide an additional option for surgical treatment of NPC in the clinic.